Evaluation of Transdermal Patches of Valproic Acid - Singh, Sudhir; Singh, Anand; Bhandari, Anil; Sharma, Satish Kumar; Singh, Sumer; Kumar, Dinesh (Asian Journal of Pharmaceutical Research and Development, 2020)
Conventional System of Medication that requires multi dose therapy are having many problems. The controlled drug delivery is a newer approach is to deliver drug into systemic circulation. As Valproic Acid is a drug to control the manic disorder so it is necessary to maintain the concentration of drug in systemic circulation continuously. So a new approach known as transdermal drug delivery system is adopted to avoid the various drawbacks of oral and other conventional dosage form.